DOC-20241230-WA0004.

Download as pdf or txt
Download as pdf or txt
You are on page 1of 15

Solution

MATHEMATICS SP 1

Class 12 - Mathematics
Section A
1.
(d) 0
Explanation:
0

2.
(d) 18
Explanation:
18

3. (a) 12

y
Explanation:

em
12
Explaination:
3 0 0
⎡ ⎤
A⋅ (adj A) = ⎢ 0 3 0⎥

0

we know that A.(AdjA) = I.|A|


0 3
⎦ d
ca
3 0 0
⎡ ⎤

⟹ ⎢0 3 0⎥ = |A| I
dA

⎣ ⎦
0 0 3

1 0 0
⎡ ⎤
⟹ 3 ⎢0 1 0⎥ = |A| I
⎣ ⎦
0 0 1

⟹ 3I = |A| I
vin

⟹ |A|=3 ---(1)
|Adj A| = |A|3-1 [ Since order n=3]
|Adj A| = (3)2=9
|adj(A)| = 9 ------(2)
Ar

Now,
|A| + |adj A| = 3 + 9 =12
4.
(d) non-singular matrix
Explanation:
non-singular matrix

5.
π
(d) 2

Explanation:

– –
Let a⃗ = ^i + ^j + 2k
^
and ^ ^ ^
b = (√3 − 1) i + (− √3 − 1) j + 4k
→ −− −−−−− −−−− −−−− −− −−−−−
– ⃗ – – –
| a | = √6 , |b| = √(4 − 2√3) + (4 + 2√3) + 16 = 2√6

^ ^ ^ ^
(^
ı +^
ȷ +2k)⋅(( √3−1) i +(− √3−1) j +4k)
cos α =
√6×2√6

√3−1− √3−1+8
cos α =
12

1 / 15
1
cos α =
2

α = 60

6.
(c) xy = C
Explanation:
xy = C

7.
(b) a feasible region
Explanation:
a feasible region

8.
(d) 5π

Explanation:

y

em
9. (a) x(log x - 1) + C
Explanation:
x(log x - 1) + C
10.
(b) -6
d
ca
Explanation:
-6
dA

11.
(c) x1 = 2, x2 = 6, Z = 36
Explanation:
vin

We need to maximize the function z = 3x1 + 5 x2


First, we will convert the given inequations into equations, we obtain the following equations: 3x1 + 2x2 = 18, x1 = 4, x2 = 6,
x1 = 0 and x2 = 0
Region represented by 3x1 + 2x2 ≤ 18
Ar

The line 3x1 + 2x2 = 18 meets the coordinate axes at A(6, 0) and B(0, 9) respectively. By joining these points we obtain the line
3x1 +
2x2 = 18
Clearly (0, 0) satisfies the inequation 3x1 + 2x2 = 18 . So, the region in the plane which contain the origin represents the
solution set of the inequation 3x1 + 2x2 = 18
Region represented by x1 ≤ 4 :
The line x1 = 4 is the line that passes through C(4, 0) and is parallel to the Y axis. The region to the left of the line x1 = 4 will
satisfy the inequation x1 ≤ 4
Region represented by x2 ≤ 6 The line x2 = 6 is the line that passes through D(0, 6) and is parallel to the x axis. The region
below the line x2 = 6 will satisfy the inequation x2 ≤ 6.
Region represented by x1 ≥ 0 and x2 ≥ 0
since, every point in the first quadrant satisfies these inequations. So, the first quadrant is the region represented by the
inequations x1 ≥ oand x2 ≥ 0
The feasible region determined by the system of constraints, 3x1 + 2x2 ≤ 18, x1 ≤ 4, x2 ≤ 6, x1 ≥ 0, and x2 ≥ 0, are as
follows :

2 / 15
Corner points are O(0, 0), D(0, 6), F(2, 6), E(4, 3) and C(4, 0).

The values of the objective function at these points are given in the following table

y
Points : Value of Z
O(0, 0) : 3(0) + 5(0) = 0

em
D(0, 6) : 3(0) + 5(6) = 30
F(2, 6) : 3(2) + 5(6) = 36
E(4, 3) : 3(4) + 5(3) = 27
C(4, 0) : 3(4) + 5(0) = 12
d
We see that the maximum value of the objective function Z is 36 which is at F(2, 6)
ca
12.
(b)
dA

11

15

Explanation:
11

15

13.
vin

11 1
(b) x = 24
,y= 24

Explanation:
11 1
x= 24
,y= 24
Ar

14.
(d) 1

Explanation:
The event happens if the two numbers a, b, (different from each other) should be chosen from the given set {1, 2, 3, 4, 5 } such
that be an integer.
a

The favorable cases may be enumerated as; 2

1
, 3

1
, 4

1
, 4

2
& 5

1
which are 5 in numbers. And total number of ways of choosing
two numbers, with order, out of 5 = 2 × C(5, 2) = 2 × ( 5!

2!
× 3!) = 20. Hence the required probability = 5

20
= 1

15.
y
(c) tan −1
(
x
) = log x + C

Explanation:
We have,
2 2
dy x +xy+ y
=
dx x2
2
dy y y

dx
= 1 +
x
+
2
...(i)
x

Let y = vx

3 / 15
dy dv
= v + x
dx dx

1 + v + v
2
= v + x
dv

dx
....from(i)
2 dv
1 + v = x
dx
dx dv
=
x 2
1+v
dx dv
∫ = ∫
x 2
1+v

log |x| = tan-1x +c

16. (a) 2π

Explanation:

17.
(c) -1
Explanation:
acos x−b sin x
Given that y = tan −1
(
b cos x+a sin x
)

Dividing by b cos x in numerator and denominator, we obtain

y
a
−tan x
−1 b
y = tan ( a
)
1+ tan x

em
b

Let a

b
= tan α ⇒ α = tan
−1 a

tan α−tan x
They y = tan −1
(
1+tan α tan x
)

tan A−tan B
Using tan (A - B) = , we obtain

y = tan-1 tan (α − x) = α − x
1+tan A tan B

= tan
−1 a

b
− x
d
ca
Differentiating with respect to x, we
dy

dx
= -1
dA

18.
(d) (3, 5, 7)
Explanation:
x−1 y−2 z−3
Let = = = λ( say )
vin

2 3 4

A general point on this line is (2λ + 1, 3λ + 2, 4λ + 3) .


For some value of λ , let the given line meet the plane 2x + 3y - z = 14 at a point P (2λ + 1, 3λ + 2, 4λ + 3).
Then, 2(2λ + 1) + 3(3λ + 2) − (4λ + 3) = 14
Ar

⇒ 9λ = 9 ⇒ λ = 1

So, the required point is P(2 + 1, 3 + 2, 4 + 3),


i.e., P(3, 5, 7).

19. (a) Both A and R are true and R is the correct explanation of A.
Explanation:
Circumference of circle with radius r is given by C = 2π r
Differentiating w.r.t. 't', we get
dC dr
= 2π
dt dt
dC
Given, dt
= 10 cm/s

dr
∴ 10 = 2π
dt
dr 5
⇒ = cm/s
dt π

Now, Area of circle, A = π r2


dA dr
∴ = 2πr
dt dt

Substituting r = 3 cm and dr

dt
=
5

π
cm/s , we get
dA 5
= 2π × 3 ×
dt π

dA 2
∴ = 30 cm /s
dt

4 / 15
20.
(d) A is false but R is true.
Explanation:
Assertion: The elements that are related to 1 will be those elements from set A which are equal to 1.
Hence, the set of elements related to 1 is {1}.
Reason: Since, R1 and R2 are equivalence relations, therefore (a, a) ∈ R , (a, a) ∈ R , ∀a ∈ A . 1 2

This implies that (a, a) ∈ R 1 ∩R2 , ∀a .


Hence, R1 ∩ R2 is reflexive.
Further, (a, b) ∈ R 1 ∩ R2 ⇒ (a, b) ∈ R and (a, b) ∈ R2 and (b, a) ∈ R2
1

⇒ (b, a) ∈ R1 ∩ R2
Hence, R1 ∩ R2 is symmetric.
Similarly, (a, b) ∈ R1 ∩ R2 and (b, c) ∈ R1 ∩ R2
⇒ (a, c) ∈ R1 and (a, c) ∈ R2 ⇒ (a, c) ∈ R 1 ∩ R2 .
This implies that R1 ∩ R2 is transitive.
Hence, R1 ∩ R2 is an equivalence relation.

y
Section B

em
1 1 −π
21. We have, tan −1
(− ) + cot
−1
( ) + tan
−1
[sin(
2
)] .
√3 √3

5π π
= tan
−1
(tan
6
) + cot
−1
(cot
3
) + tan
−1
(−1) .
−1 π −1 π −1
ad π
= tan [tan(π − )] + cot [cot( )] +tan [tan(π − )]
6 3 4

−1
π π
⎡ ∵ tan (tan x) = x, x ∈ (− , ) ⎤
2 2
−1 π −1 π −1 π ⎢ ⎥
= tan (− tan ) + cot (cot ) + tan (− tan ) ⎢ −1 ⎥
6 3 4 ⎢ cot (cot x) = x, x ∈ (0, π) ⎥
Ac
⎣ −1 −1 ⎦
and tan (−x) = − tan x
π π π −2π+4π−3π
= − + − =
6 3 4 12
−5π+4π −π
= =
12 12

OR
d

Principal value branch of cos-1 x is [0, π ] and its graph is shown here,
vin
Ar

22. It is given that f(x) = cos2 x + sin x, x ∈ [0, π]


f (x) = 2 cos x (-sin x) + cos x

= -2 sin x cos x + cos x


Now, if f (x) = 0 ′

⇒ 2 sin x cos x = cos x

⇒ cos x (2 sin x - 1) = 0

⇒ sin x = or cos x = 0
1

⇒ x =
π

6
,

6
or π

2
as x ∈ [0, π]
Next, evaluating the value of f at critical points x = π

2
and x = π

6
and at the end points of the interval [0, π] , (i.e. at x = 0 and
x = π ), we get,
2
π π π √3 1 5
2
f ( ) = cos + sin = ( ) + =
6 6 6 2 2 4

5π 2 5π 5π 2 π π 2 π π 5
f( ) = co s ( ) + sin( ) = co s (π − ) + sin(π − ) = co s − sin =
6 6 6 6 6 6 6 4

5 / 15
f(0) = cos2 0 + sin 0 = 1 + 0 = 1
f (π) = cos
2
π + sin π = (-1)2 + 0 = 1
π 2 π π
f ( ) = cos + sin = 0 + 1 = 1
2 2 2

Therefore, the absolute maximum value of f is 5

4
occurring at x = π

6
and the absolute minimum value of f is 1 occurring at x = 1,
π

2
and π .
WL W
23. Given: M = 2
x −
2
x
2

dM WL Wx
⇒ = −2 ×
dx 2 2
dM WL

dx
= 2
− Wx

For maximum or minimum values of M, we must have


dM

dx
=0

WL

2
- Wx = 0

WL

2
= Wx
L
⇒ x= 2

Now,
2
d M

2
= -W < 0
dx

So, M is maximum at x = L
.

y
2

OR

em
Given curve is,
6y = x3 + 2
dy dx
⇒ 6
dt
= 3x 2

dt
... (i)
dy
Given: dt

from (i) and (ii), 2 (2


=2 ⋅
dx

dt
... (ii)
dx
) =x 2

dx
d
ca
dt dt

⇒ x = ±2
5
when x = 2, y = 3
; when x = –2, y = -1
dA

Therefore, Points are (2, 5

3
) and (-2, -1)
1
log 3 x

24. ∫
0
2 e

2x
dx
1+e
1
log 3 x
2 e
∫ dx
vin

0 x 2
1+( e )

Put ex = t, exdx=dt
Changing limit
at x = 0, t = e0 = 1
Ar

1
log 3 –
at x = 1

2
log 3 ,t=e 2 = e
log √3
= √3

So,
√3 dt √3
−1
∫ = [ tan t]
1 2 1
1+t

−1 – −1 π π
= [ tan √3 − tan 1] = −
3 4
π
=
12

25. Given,f(x) = 2x3 + 9x2 + 12x + 15


f’(x) = 6x2 + 18x + 12
f’(x) = 6(x2 + 3x + 2)
= 6(x + 2)(x + 1)

Therefore,function f(x) is decreasing for x ∈ [-1, -2] and increasing in x ∈ (−∞, −1) ∪ (−2, ∞)
Section C
−−−−−−−− −
26. I = ∫√5 − 4x − x2 dx
−−−−−−−−−−−−−−−−−− −
2
I = ∫ √− (x + 4x + 4 − 4 − 5) dx
−−−−−−−−−− −
2
I = ∫ √− (x + 2) + 9 dx

6 / 15
−−−−−−−−−−−−
2 2
I = ∫ √(3) − (x + 2) dx

−−−−−−−−−
−−−−−− 2

As, ∫ √(a)
2
− (x)
2
dx =
x

2
√a2 − x2 +
a

2
sin
−1 x

a
+ C

−−−−−−−−−−−−
x+2 −−−−−−−− − x+2
So, ∫ √(3)
2
− (x + 2)
2
dx =
2
√5 − 4x − x2 +
9

2
sin
−1

3
+ C

27. Let us define the following events:


E1 : Bag X is selected
E2 : Bag Y is selected
and E: Getting one white and one black ball in a draw of two balls.
Here,P (E ) = P (E ) = 1 2
1

[·:probability of selecting each bag is equal]


Now, P ( E

E1
) = Probability of drawing one white and one black ball from bag X
4 2
C1 × C1 4×2 16 8
= = = =
6 6×5 6×5 15
C2
2×1

and P ( E

E2
) = Probability of drawing one white and one black ball from bag Y
3 3
C1 × C1 3×3 3
= = =
6 6×5 5

2×1

y
The probability that the one white and one black balls are drawn from bag Y
E

em
P ( E2 )⋅P ( )
E2 E
2
F ( ) =
E E E
P ( E1 )⋅P ( )+P ( E2 )⋅P ( )
E E
1 2

[by using Baye's theorem]


1 3 3 3
×

=
1

2
×
2

15
+
5

2
×
3

5
=
8

15
5

+
3

5
=
8+9

8+9
5
=

3

17

15
=
9

17
.
ad
15
a a
28. We have to show ∫ f (a − x)dx =∫ f (x)dx
Ac
0 0
a
Take I = ∫ 0
f (a − x)dx ......(i)
Let a - x = z ⇒ -dx = dz ⇒ dx - dz
Also, x = 0 ⇒ z = a and x = a ⇒ z = 0
0 0
∴ I=∫ a
f (z)(−dz) =∫ a
f (z)dz
d

a b a
⇒ I=∫ 0
f (z)dz (∵ ∫ a
f (x)dx = −∫ 0
f (x)dx
a b b
I=∫ .....(ii) (∵ ∫ =∫
vin

⇒ f (x)dx f (z)dz f (x)dx


0 a a

From (i) and (ii), we get


a a
∫ (a − x)dx = ∫ f (x)dx
0 0
π

x
Now, ∫ 2
dx ......(iii)
Ar

0 sin x+cos x
π
( −x)
π/2
I=∫ =
2 π 1
⇒ dx ∫ dx
0 x x 2√2 1 1
sin( −x)+cos( −x) cos x +sin x
2 2 √2 √2
π

= π

0
2
π
1
π
dx
2√2 sin x sin +cos x cos
4 4
π

π 1
= ∫
0
2
π dx
2√2 cos(x− )
4
π

2I = π

0
2
sec(x +
π

4
)dx
2√2
π

= π
[log(sec x + tan x)]
2

0
2√2

= π
[log (sec π

2
+ tan π

2
) - [log (sec 0 + tan 0)]
2√2

π
2I = [∞ - log 1] = ∞
2√2

I=∞
OR
x
(x+3)e
Let the given integral be, l = ∫ 3
dx
(x+5)

(x+5)−2
⇒ I=∫ [
3
] e dx
x

(x+5)

7 / 15
−2
⇒ I=∫ [
1

2
+
3
] e dx
x

(x+5) (x+5)

⇒ ∫
1

2
e dx
x
-∫ 2

3
e dx
x

(x+5) (x+5)

using parts method for 1st part and keep 2nd part as it is we get.

⇒ I= 1

2
∫ e dx
x
-∫ [
d

dx
(
1

2
) ∫ e dx] dx
x
-∫ 2

3
x
e dx
(x+5) (x+5) (x+5)

1 2 2 1
⇒ I= 2
e
x
+∫ 3
e dx
x
-∫ 3
x
e dx = 2
e
x
+C
(x+5) (x+5) (x+5) (x+5)

−2√x y
e dx
29. ( − ) =1
√x √x dy

dy −2√x y
e
= −
dx √x √x

dy y −2√x
e
+ =
dx √x √x

Given differential equation is of the form:


dy
+ Py = Q
dx
1
∫ dx
√x 2√x
I. F = e = e

Solution is,
−2√x
2√x 2√x e
y × e = ∫ e × dx + c

y
√x

2√x 1
ye = ∫ dx + C
√x

em
2√x −
ye = 2√x + C

OR
The given differential equation is,
dy
x + y = x log x


dx
dy

dx
+
1

x
y = log x
ad
dy
This is of the form dx
+ Py = Q
Ac
1
where P = and q = log x x

Thus the given differential equation is linear


1

Now, I F = e
∫ P dx
= e

x
dx
= e
log x
= x

y ⋅ (I F ) = ∫ (I F )Q dx + C
d

d
⇒ xy = log x ∫ x dx − ∫ { (log x)dx} dx + C
dx

2 2
vin

x 1 x
⇒ xy = log x − ∫ ⋅ dx + C
2 x 2
2 2
x x
⇒ xy = ⋅ log x − + C
2 4

⇒ 4xy = 2x2 log x- x2 + C 1 ,where C =4C 1

30. Our problem is to minimise the objective function Z = 5x + 10 y ...(i)


Ar

Subject to constraints
x + 2y ≤ 120......(ii)
x + y ≥ 60........(iii)
x -2y ≥ 0..........(iv)
x ≥ 0, y ≥ 0 ( which is the non negative constraint which will restrict the feasible region to the first quadrant only)
Table of values for line ( ii) x + 2y = 120 are given below.
x 0 120

y 60 0
Replace O (0, 0) in the inequality x + 2y ≤ 120, we get
0 + 2 × 0 ≤ 120
⇒ 0 ≤ 120 (which is true)

So, the half plane for the inequality of the line ( ii) is towards the origin which means that the origin O(0,0) is a point in the
feasible region of the inequality of the line ( ii).
Secondly, draw the graph of the line x + y = 60.Hence the table of values of the line ( iii) is given as follows.
x 0 60

y 60 0

8 / 15
On replacing O(0, 0) in the inequality x + y≥ 60, we get
0 + 0 ≥ 60 ⇒ 0 ≥ 60 (which is false)

So, the half plane for the inequality of the line ( iii) is away from the origin, which means that the origin is not a point on the
feasible region .
Thirdly, draw the graph of the line x - 2y = 0 and the table of values for ( iv) is given as follows.
x 0 10

y 0 5

On solving equations x - 2y = 0 and x + y = 60, we get D(40,20) and on solving equations x -2y = 0 and x + 2y = 120, we get C

y
(60, 30)
Feasible region is ABCDA, which is a bounded feasible region, the coordinates of the corner points of the feasible region are

em
given as A (60, 0), B ( 120, 0), C ( 60, 30) and D (40, 20).
Corner points Z = 5x + 10y

A(60,0) ad Z = 300(minimum)

B(120,0) Z= 600

C(60,0) Z= 600
Ac
D(40,20) Z= 400
The values of Z at these points are as follows So, the minimum value of Z is obtained as 300 , which occurs at the point (60, 0).
OR
The linear inequations or constraints
d

x + 3y ≤ 60
vin

x + y ≥ 10

x ≤ y

x ≥ 0, y ≥ 0 and objective functions is max or min (Z) = 3x + 9y


Reducing the above inequations into equations and finding their point of intersection i.e.,
Ar

x + 3y = 60 ... (i)

x + y = 10 ... (ii)

x = y ... (iii)
x = 0, y = 0 ... (iv)
Equations Point of Intersection

(i) and (ii) x = −15, y = 25

Point is ⇒ (−15, 25)

(i) and (iii) x = 15 ⇒ y = 15

Point is ⇒ (15, 15)

(ii) and (iii) x = 5, y = 5

Point is (5, 5)

(i) and (iv) when x = 0 ⇒ y = 20,

Point is(0, 20)

when y = 0 ⇒ x = 60,

9 / 15
Point is (60, 0)

(ii) and (iv) when x = 0 ⇒ y = 10,

Point is (0, 10)

when y = 0 ⇒ x = 10,

Point is (10, 0)
Now for feasible region,
For x + 3y ≤ 60 , putting x = 0 and y = 0, we have
0 + 0 ≥ 10 i.e., Not true

⇒ The shaded region will be away from origin.


Also, we have x ≥ 0 , and y ≥ 0 indicates that the shaded part will exist in first quadrant only. Here feasible region will be
ABCDA, having corner points as A(0, 20), B(15, 15), C (5, 5) and D(0, 10) .
For optimal point substituting the value of all corner points in objective function Z = 3x + 9y
Corner points Z

A(0, 20) 180


Maximum

y
B(15, 15) 180

em
C (5, 5) 60
Minimum
D(0, 10) 90

So that the minimum value of Z is 60 at C (5, 5) of the feasible region and the maximum value at A (0, 20) and B(15, 15) is Z =
180.
ad
d Ac
vin

31. According to the question, y = x x

Taking log both sides,


Ar

x
⇒ log y = log x

⇒ log y = xlog x

Differentiating both sides w.r.t. x,


dy

1

y
= x
d
(log x) + log x
d
(x) [Using product rule of derivative]
dx dx dx

1 dy 1
⇒ = x × + log x ⋅ 1
y dx x

1 dy
⇒ = (1 + log x)
y dx
dy

dx
= y(1 + log x) .......(i)
Differentiating both sides w.r.t. x,
2
d y dy

2
= y
d

dx
(1 + log x) + (1 + log x)
dx
[Using product rule of derivative]
dx
2
d y 1 dy
⇒ = y × + (1 + log x)
2 x dx
dx
2
d y y dy
⇒ = + (1 + log x)
2 x dx
dx
2
d y y dy dy

2
=
x
+
1

y
(
dx
)(
dx
) [ Using Equation(i)]
dx

2 2
d y 1 dy y
∴ − ( ) − = 0
2 y dx x
dx

Hence Proved
Section D

10 / 15
32. According to Given question , Region is {(x, y) :x2 + y2 ≤ 4, x + y≥ 2}.
The above region has a circle with equationx + y = 4 .....(i) 2 2

centre of the given circle is (0, 0)


Radius of given circle = 2
The above region consists of line whose equation is
x + y = 2 .......(ii)
Point of intersection of line and circle is
⇒ x2 + (2 - x)2 = 4 [from Eq. (ii)]
⇒ x2 + 4 + x2 - 4x = 4
⇒ 2x2 - 4x = 0
⇒ 2x (x - 2) = 0

⇒ x = 0 or 2

When x = 0, then y = 2 - 0 = 2
When x = 2, then y = 2 - 2 = 0
So, points of intersection are (0, 2) and (2, 0).
On drawing the graph, we get the shaded region as shown below:

y
em
ad
Ac
2
Required area=∫ 0
[y
( circle ) − y
(line) ] dx

2 −−−−−
= ∫
0
2
[ √4 − x − (2 − x)] dx [From Eq(i) and (ii)]
2 −−−−− 2
= ∫ √4 − x2 dx − ∫ (2 − x)dx
0 0
d

2 2
x
−−−−− 4 −1 x
2
x
−− −−−− x
−−−−−− 2
a −1 x
= [ √4 − x2 + sin ] −[2x −
2 2
] [∵ √a − x dx = √a2 − x2 + sin ( )]
2 2 2 2 2 2 a
0 0
vin

−1 2 −1 4
= [0 + 2 sin ( ) − 0 − 2 sin 0] − (4 − − 0)
2 2

−1 4
= (2 sin −0) − (4 − )
2

π
= 2 ⋅ − 2
2
Ar

= (π − 2) sq units

33. Given that A = {1, 2, 3, 4},


a. Let R1 = {(1,1), (1,2), (2,3), (2,2), (1,3), (3,3)}
R1 is reflexive, since, (1,1) (2,2) (3,3) lie is R1
Now, (1,2) ∈ R1 (2,3) ∈ R1 ⇒ (1, 3) ∈ R1
Hence, R1 is also transitive but (1,2), ∈ R1 ⇒ (2,1) ∉ R1
So, it is not symmetric.
b. Let R2 = {(1,2),(2,1)}. Here,1,2,3 ∈ {1,2,3} but (1,1),(2,2),(3,3) are not in R.
Therefore, R is not reflexive.Now, (1,2) ∈ R2, (2,1) ∈ R2
So, it is symmetric.
Now (1,2) ∈ R (2,1) ∈ R, but (1,1) ∉ R,
therefore, R is not transitive.
c. Let R3 = {(1,2), (2,1),(1,1)(2,2),(3,3),(1,3),(3,1),(2,3)}
Clearly, R3 is reflexive, symmetric and transitive.
OR

11 / 15
We have, A = {x ∈ Z : 0 ≤ x ≤ 12} be a set and
R = {(a, b) : a = b} be a relation on A
Now,
Reflexivity: Let a ∈ A
⇒ a = a

⇒ (a, a) ∈ R

⇒ R is reflexive

Symmetric: Let a, b, ∈ A and (a, b) ∈ R


⇒ a=b
⇒ b=a
⇒ (b, a) ∈ R

⇒ R is symmetric

Transitive: Let a, b & c ∈ A


and let (a, b) ∈ R and (b, c) ∈ R
⇒ a = b and b = c
⇒ a = c

⇒ (a, c) ∈ R

y
⇒ R is transitive

Since R is being reflexive, symmetric and transitive, so R is an equivalence relation.

em
Also we need to find the set of all elements related to 1.
Since the relation is given by, R = {(a, b): a = b}, and 1 is an element of A.
R = {(1, 1): 1 = 1}
Thus, the set of all elements related to 1 is {1}.

2 −3 5

ad
34. A = ⎢ 3 2 −4 ⎥
⎣ ⎦
Ac
1 1 −2

∴ |A| = 2(-4 + 4) + 3(-6 +4)+ 5(3 - 2) = 0 -6 +5 = -1


Now, A11 = 0, A12= 2, A13= 1
A21= -1, A22 = -9, A23= -5
A31= 2, A32= 23,A33 = 13
d

0 −1 2 0 1 −2
⎡ ⎤ ⎡ ⎤
vin

∴ A
−1
=
1
(adjA) = − ⎢ 2 −9 23 ⎥ = ⎢ −2 9 −23 ⎥ ....(1)
|A|
⎣ ⎦ ⎣ ⎦
1 −5 13 −1 5 −13

Now, the given system of equations can be written in the form of AX = B, where
2 −3 5 x 11
⎡ ⎤ ⎡ ⎤ ⎡ ⎤
Ar

A= ⎢3 2 −4 ⎥ , X = ⎢ y ⎥ and B = ⎢ −5 ⎥
⎣ ⎦ ⎣ ⎦ ⎣ ⎦
1 1 −2 z −3

The solution of the system of equations is given by X = A-1B


x 0 1 −2 11
⎡ ⎤ ⎡ ⎤⎡ ⎤
⇒ ⎢ y ⎥ = ⎢ −2 9 −23 ⎥ ⎢ −5 ⎥ [Using (1) ]
⎣ ⎦ ⎣ ⎦⎣ ⎦
z −1 5 −13 −3

0 − 5 + 6
⎡ ⎤

= ⎢ −22 − 45 + 69 ⎥
⎣ ⎦
−11 − 25 + 39

1
⎡ ⎤

= ⎢2⎥

⎣ ⎦
3

Hence, x = 1, y = 2 and z = 3.​​


35. Given lines are r ⃗ = (^i + ^j − k
^ ^ ^
) + λ(3 i − j )

and r ⃗ = (4^i − k
^ ^ ^
) + μ(2 i + 3k)

On comparing both equations of lines with


r ⃗ = a⃗ + λb

respectively, we get ,


^ ^ ^ ^ ^
a1 = i + j − k, b1 = 3 i − j

12 / 15


and a 2
^ ^ ^ ^
= 4 i − k, b2 = 2 i + 3k

∣^ ^ ^∣
i j k
→ → ∣ ∣
Now b1 × b2 = ∣ 3 −1 0∣
∣ ∣
∣2 0 3∣

^ ^ ^
= i (−3 − 0 − j (9 − 0) + k(0 + 2)

^ ^ ^
= −3 i − 9 j + 2k
→ →
and a 2
^ ^ ^ ^ ^ ^ ^
− a1 = (4 i − k) − ( i + j − k) = 3 i − j

Now, (a⃗ 2
⃗ ⃗ ^ ^ ^ ^ ^
− a⃗1 ) ⋅ (b1 × b2 ) = (3 i − j ) (−3 i − 9 j + 2k) .
=-9+9=0
Hence, given lines are coplanar.
Now, cartesian equations of given lines are
x−1 y−1 z+1
= =
3 −1 0

x−4 y−0 z+1


and 2
=
0
=
3

Then, equation of plane containing them is


∣ x − x1 y − y1 z − z1 ∣
∣ ∣
a1 b1 c1 = 0

y
∣ ∣
∣ a2 b2 c2 ∣

em
∣x − 1 y − 1 z+ 1∣
∣ ∣
⇒ 3 −1 0 = 0
∣ ∣
∣ 2 0 3 ∣

(x - 1 ) (-3- 0) - ( y - 1 ) (9- 0)+(z+1)(0+2)=0 ad


- 3x + 3 - 9y + 9 + 2z + 2 = 0
3x + 9y - 2z = 14
OR
Ac

^ ^ ^
a 1 = −i − j − k

^ ^ ^
a 2 = 3 i + 5 j + 7k

^ ^ ^
b 1 = 7 i − 6 j + 1k

^ ^ ^
d

b 2
= i − 2j + k

→ →
^ ^ ^
a 2 − a 1 = 4 i + 6 j + 8k
vin

∣^ ^ ^∣
i j k
→ → ∣ ∣
b 1 × b 2 = ∣7 −6 1∣
∣ ∣
∣1 −2 1∣

^ ^ ^
= −4 i − 6 j − 8k
Ar

⃗ ⃗ ^ ^ ^ ^ ^ ^
(a⃗2 − a⃗1 ). (b1 × b2 ) = (4 i + 6 j + 8k). (−4 i − 6 j − 8k) = -16 - 36 - 64 = -116
−−−−−−−−−−−−−−−−−−
∣→ → ∣
2 2 2
∣ b 1 × b 2 ∣ = √(−4) + (−6) + (−8)
∣ ∣
−−−
= √116
−−
= 2√29

∣ ∣
→ →
∣ ( a 2 − a 1 ).( b1 × b2 ) ∣
d =
∣ ∣→ → ∣ ∣
∣ b 1× b 2∣
∣ ∣ ∣ ∣

∣ −116 ∣ 4×29
= =
∣ 2√29 ∣ 2√29
−−
= 2√29

Section E
36. i. Bayes' theorem defines the probability of an event based on the prior knowledge of the conditions related to the event whereas
in case of the condition probability, we find the reverse probabilities using Bayes' theorem.
ii. Consider on event E which occurs via two different events A and B. The probability of E is given by the value of total
probability as:
P(E) = P(A ∩ E) + P(B ∩ E)
P(E) = P(A) P( E

A
) + P(B)( E

B
)

13 / 15
iii. Let P be the event that the shell fired from A hits the plane and Q be the event that the shell fired from B hits the plane. The
following four hypotheses are possible before the trial, with the guns operating independently:
E1 = PQ, E2 = P¯Q¯
, E3 = P¯Q, E4 = PQ ¯

Let E = The shell fired from exactly one of them hits the plane.
P(E1) = 0.3 × 0.2 = 0.06,
P(E2) = 0.7 × 0.8 = 0.56,
P(E3) = 0.7 × 0.2 = 0.14,
P(E4) = 0.3 × 0.8 = 0.24
P( E

E1
) = 0, P( E

E2
) +0, P( E

E3
) = 1, P( E4
E
) =1

P(E) = P(E1) ⋅ P( E

E1
) + P(E2) ⋅ P( E

E2
) + P(E3).

P( E

E3
) + P(E4) ⋅ P( E

E4
)

= 0.14 + 0.24 = 0.38


OR
By Bayes' Theorem,
i. P(Shell fired from exactly one of them hits the plane)

y
= P[(Shell from A hits the plane and Shell from B does not hit the plane) or (Shell from A does not hit the plane and Shell
from B hits the plane)]

em
= 0.3 × 0.8 + 0.7 × 0.2 = 0.38
P(Shell fired from B hit the plane ∩ Exactly one of them hit the plane)
ii.
P(Exactly one of them hit the plane)
P (Shell from only B hit the plane )
=
=
P

0.14
(Exactly one of them hit the plane )
=
7
ad
0.38 19

E
Ac
P ( E3 )⋅P ( )
E3 E3

iv. P( E
) =
E E E E
P ( E1 )⋅P ( )+P ( E2 )⋅P ( )+P ( E3 )P ( )+P ( E4 )⋅P ( )
E1 E2 E3 E4

0.14 7
= =
0.38 19

NOTE: The four hypotheses form the partition of the sample space and it can be seen that the sum of their probabilities is 1.
d

The hypotheses E1 and E2 are actually eliminated as P( E

E1
) = P( E

E2
) =0
vin

Alternative way of writing the solution:


→ → →
37. i. Total displacement = | d 1| + | d2 | + | d3 |
→ −− −−−−
2 2
| d1 | = √6 + 8
−−−−−−
= √36 + 64
Ar

−−−
= √100
= 10 km
→ −− −−−−
2 2
| d2 | = √3 + 4
−−−−−
= √9 + 16
−−
= √25
= 5 km
→ −− −−−−−
2 2
| d3 | = √7 + 12
−−−−−−−
= √49 + 144
= 13.89
Total displacement = 10 + 5 + 13.89
= 28.89
≈ 29 km
Total distance
ii. Speed = = Total time
28.89
= 1.5

= 19.26 km/hr

14 / 15
iii. Displacement form village to zoo = d1 + d2
= 10 + 5
= 15 km
OR
Displacement from temple to mall = d2 + d3
= 5 + 13.89
= 18.89
≈ 19 km

38. i. If P is the rent price per apartment and N is the number of rented apartments, the profit is given by NP - 500 N = N(P - 500)
[∵ ₹500/month is the maintenance charge for each occupied unit]
ii. Let R be the rent price per apartment and N is the number of rented apartments.
Now, if x be the number of non-rented apartments, then N(x) = 50 - x and R(x) = 10000 + 250x
Thus, profit = P(x) = NR = (50 - x) (10000 + 250 x - 500)
= (50 - x) (9500 + 250 x) = 250(50 - x) (38 + x)
iii. We have, P(x) = 250(50 - x) (38 + x)
Now, P'(x) = 250[50 - x - (38 + x)] = 250[12 - 2x]
For maxima/minima, put P'(x) = 0

y
⇒ 12 - 2x = 0 ⇒ x = 6

em
Number of apartments are 6.
OR
P′(x) = 250(12 - 2x)
P′′(x) = - 500 < 0 ad
⇒ P(x) is maximum at x = 6
d Ac
vin
Ar

15 / 15

You might also like

pFad - Phonifier reborn

Pfad - The Proxy pFad of © 2024 Garber Painting. All rights reserved.

Note: This service is not intended for secure transactions such as banking, social media, email, or purchasing. Use at your own risk. We assume no liability whatsoever for broken pages.


Alternative Proxies:

Alternative Proxy

pFad Proxy

pFad v3 Proxy

pFad v4 Proxy